Avaliação da eficácia da técnica de relaxamento com imagem guiada em pacientes oncológicos submetidos a tratamento quimioterápico - Lufiego, Claudia Adriana Facco (2017)
To evaluate the efficacy of the guided imaging relaxation technique in cancer patients submitted to chemotherapy in relation to decreasing levels of depression, anxiety and stress. Methods: Non-randomized clinical trial type study. The sample consisted of participants of both sexes, and aged 30 years or more starting chemotherapy treatment in a university hospital in Porto Alegre. The patients were divided into two groups: Experimental Group, in which the relaxation technique was applied, and Control Group, without the intervention. The relaxation sessions with the guided imaging technique had a duration of 12 minutes and were performed during a period of 16 weeks, always during the chemotherapy procedure. In order to evaluate the levels of depression, anxiety and stress were applied the instruments Beck Depression Inventory, Beck Anxiety Inventory and Distress Thermometer respectively, in the initial and final period of the study. Data were analyzed in the EpiInfo7.0 statistical software using Student's t-tests, Wilcoxon-Mann-Whitney and Pearson's Chi-square. Values of p <0.05 were considered significant. Results: Onehundred thirteen participants were included, with a mean age of 51.3 years, 62.8% were female and 72.6% married. The most prevalent types of neoplasia were breast, lung and intestine cancers. Fifty-seven patients participated in the Experimental Group and 56 patients in the Control Group. There was a decrease in depression, anxiety and stress levels in the Experimental Group, with a range of depression scores ranging from 17.3 ± 9.04 to 14.5 ± 7.47 (p<0.0001), anxiety of 15.1 ± 8.84 to 12.9 ± 7.58 (p<0.0001) and for stress 5.1228 ± 1.8905 for 4.4386 ± 1.6905 (p<0.0001). In the Control Group, no significant difference was observed between the initial and final evaluation. Conclusions: the intervention through the relaxation technique with guided imagery showed efficacy in reducing the levels of depression, anxiety and stress in this sample of cancer patients undergoing chemotherapy.